Franklin has a sleepover - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic Inc., 1998)
Franklin invites his best friend, Bear, to a sleepover, the very first for each of them.
RL: 2 004-007.
Keywords: Franklin -- (Fictitious character from Bourgeois) -- Juvenile fiction; Sleepovers -- Juvenile fiction; Turtles -- Juvenile fiction; Bears -- Juvenile fiction; Sleepovers -- Fiction; Turtles -- Fiction; Bears -- Fiction